(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Burns are a global public health problem, accounting for an estimated 180,000 deaths annually.1 The majority of these occur in low- and middle-income countries and almost two thirds occur in the WHO African and South-East Asia Regions. Non-fatal burns are a leading cause of morbidity, including prolonged hospitalization, disfigurement and disability, often with resulting stigma and rejection. According to the Na tional Burns Programme, 91,000 of these deaths are women; a figure higher than that for maternal mortality. Women of child bearing age are on average three times more likely than men to die of burn injuries. Females have slightly higher rates of death from burns compared to males. This contrasts with the usual injury pat tern, where rates of injury for the various injury mechanisms tend to be higher in males than females.2 Along with adult women, children are particularly vulnerable to burns. Burns are the fifth most common cause of non-fatal childhood injuries.3 Methods: Retrospective study involving 53 cases of burn injuries were included in this study over a period of 3 years. Results: Out of 53 cases, 37 individuals were females depicting female preponderance.